Breeding goals and strategies for improving small ruminant productivity in African input systems - Ojango, Julie M.K.; Osei-Amponsah, R.; Houaga, I.; Gondwe, T.; Okpeku, M.; Kugonza, D.R. (Springer, 2025)
Africa’s sheep and goat genetic resources are well adapted to their production environments, are important components of the food basket, a source of employment and wealth and fulfil socio-cultural and religious roles. This chapter provides information on the key components of sheep and goat breeding programmes, including various technologies adapted in breeding programmes in Africa. Section 17.1 presents a general overview of sheep and goat production in Africa to contextualize the importance of sheep and goat breeding programmes for the continent. This is followed by an outline of the key components required to define breeding goals for sheep and goats with examples of parameters developed and breeding practices adopted in different sheep and goat populations in Africa in Sect. 17.2. Breed-specific examples of successful breeding programmes and the lessons learned in relation to genotype–environment interaction, socio-economic aspects, and various strategies to ensure sustainable use and conservation of sheep and goat in Africa are discussed in Sects. 17.3 and 17.4. The final sections of this chapter (Sects. 17.5 and 17.6) present an overview of external factors that influence breeding structures and opportunities for adopting new technologies in sheep and goat improvement in Africa. An important recommendation is the need for governments in Africa to invest in human and institutional capacity development, encourage public–private partnerships, and embrace technological innovations in small ruminant production.